2015
DOI: 10.1016/j.cej.2015.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pretreatment methods for improving microalgae anaerobic digestion: Thermal, hydrothermal, microwave and ultrasound

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. lipids. This was attributed to the macromolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(72 citation statements)
references
References 20 publications
3
67
2
Order By: Relevance
“…Ultrasound microalgae pretreatment has been mainly applied for biodiesel, bioethanol, and biogas production and has been proven to adequately break algal cells in low concentration biomass suspension. Passos et al (2015a) reported that ultrasound pretreatment (20 kHz, 30 min, 26.7 MJ/kg TS) increased the soluble fraction of organic matter, proteins, carbohydrates, and lipids 7-, 12-, 9-, and 3-fold compared to untreated samples. Likewise, Silva et al (2014) applied ultrasounds (40 kHz, 60 min) on a mixed microalgae culture composed of Chlorophyceae, Cyanophyceae, Euglenophyceae, and Bacillariophyceae, obtaining lipid extraction yields of 13.3%.…”
Section: Physical Methods For Cell Wall Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound microalgae pretreatment has been mainly applied for biodiesel, bioethanol, and biogas production and has been proven to adequately break algal cells in low concentration biomass suspension. Passos et al (2015a) reported that ultrasound pretreatment (20 kHz, 30 min, 26.7 MJ/kg TS) increased the soluble fraction of organic matter, proteins, carbohydrates, and lipids 7-, 12-, 9-, and 3-fold compared to untreated samples. Likewise, Silva et al (2014) applied ultrasounds (40 kHz, 60 min) on a mixed microalgae culture composed of Chlorophyceae, Cyanophyceae, Euglenophyceae, and Bacillariophyceae, obtaining lipid extraction yields of 13.3%.…”
Section: Physical Methods For Cell Wall Disruptionmentioning
confidence: 99%
“…Apart from biomass concentration, pretreatment time and power of microwaves are the main operation parameters. Passos et al (2015a) used microwaves to increase the soluble fraction of organic matter, proteins, carbohydrates, and lipids by a factor of 8, 18, 12, and nearly 2, respectively, compared to the untreated biomass. Silva et al (2014) applied a microwave pretreatment (400 W, 4 min) on mixed culture biomass of Chlorophyceae, Cyanophyceae, Euglenophyceae, and Bacillariophyceae and reported a remarkably higher lipid extraction (33.7%) compared to the untreated sample (4.8%).…”
Section: Physical Methods For Cell Wall Disruptionmentioning
confidence: 99%
“…When the air load was 12.5 mL/L R -d, cumulative methane yield reached maximum, which was 216.8 mL/g VS substrate and 16.5% higher than that of sample under anaerobic condition. Improved methane yield from cellulosic substrate after pretreatment has also been reported by other authors [24][25][26]. Though the improvements were different, (this has something to do with the composition of the substrate and the different operational conditions [24]) these methods all can accelerate the hydrolysis process by destroying the substrate Fig.…”
Section: The Effect Of Microaerobic Condition On the Thermophilic Fermentioning
confidence: 61%
“…AD offers an alternative option for converting microalgal biomass in its entirety (without the need for any prior drying for water removal and/or prior pre-treatment steps) into a final product of useable energy [171]. Nevertheless, due to the complex structure and composition of the microalgal cell wall which hinders the initial hydrolysis step, pre-treatment methodologies have also been applied to improve the ultimate methane production yields and the biodegradability of the biomass [172]. In the work of Passos et al [173], the specific energy (regardless of the output power and exposure time) of the MW pre-treatment on microalgae biomass cultivated in High Rate Algal Ponds (HRAP), played an important effect on biomass solubilisation and final methane yields.…”
Section: Mw Pre-treatment For Biogas Production Via Anaerobic Digestionmentioning
confidence: 99%